Assessment of Pain Response in Capsaicin-Induced Dynamic Mechanical Allodynia Using a Novel and Fully Automated Brushing Device. (2013) - du Jardin, Kristian G; Gregersen, Lise S; Røsland, Turid; Uggerhøj, Kathrine H; Petersen, Lars J; Arendt-Nielsen, Lars; Gazerani, Parisa
Abstract : BACKGROUND: Dynamic mechanical allodynia is traditionally induced by manual brushing of the skin. Brushing force and speed have been shown to influence the intensity of brush-evoked pain. There are still limited data available with respect to the optimal stroke number, length, force, angle and speed. Therefore, an automated brushing device (ABD) was developed, for which brushing angle and speed could be controlled to enable quantitative assessment of dynamic mechanical allodynia. OBJECTIVES: To compare the ABD with manual brushing using capsaicin-induced allodynia, and to investigate the role of stroke angle and speed on pain intensity. METHODS: Experimental dynamic mechanical allodynia was induced by an intradermal injection of capsaicin (100 μg) into the volar forearm of 12 healthy, male volunteers. Dynamic mechanical allodynia was rated on a 10 cm visual analogue scale (VAS) after each set of strokes at angles of 30°, 60° and 90° with speeds of 17 mm/s, 21 mm/s and 25 mm/s for each angle. A two-way ANOVA with repeated measures was performed to assess the influence of brushing parameters. To evaluate test-retest reliability, Bland-Altman 95% limits of agreement, including a coefficient of repeatability and an intraclass correlation coefficient (ICC), were determined. RESULTS: The angle and speed exhibited a significant impact on pain intensity (P<0.001 and P<0.015, respectively). Post hoc analysis showed that the highest pain intensity was recorded with an angle of 30° regardless of brushing speed. The ABD demonstrated superior test-retest reliability (coefficient of repeatability = 1.9 VAS; ICC=0.91) compared with manual brushing (coefficient of repeatability = 2.8 VAS; ICC=0.80; P<0.05). The most reliable combination of parameters (coefficient of repeatability = 1.3 VAS; ICC=0.97) was an angle of 60° and a speed of 21 mm/s. CONCLUSIONS: A controlled, automatic brushing method can be used for quantitative investigations of allodynic reactions, and is more reliable for quantitative assessment of dynamic mechanical allodynia compared with traditional manual brushing.